Role of Workers’ Remittances in Export Performance of Nepal: Gravity Modelling Approach - Paudel, Ramesh Chandra; Bhusal, Tara Prasad (NRB Economic Review, 2021)
Role of workers’ remittance seems to be an imperative part of Nepalese economy for about two decades. The remittances inflow has supported to maintain the foreign reserves at the national level and consumption in household level. This paper investigates the role of remittances in export performance of Nepal employing the gravity modelling approach using annual data for the period of 26 years, from year 1993 to 2018. First, we document the scenario of remittances and export nexus, then conduct an econometric estimation for the exports flows from Nepal to its trading partners. The major finding indicates that the remittances have a statistically significant negative impact on export performance, which is largely impacted by the size of the trading partner’s economy as indicated by the estimation’s results. The study suggests for an urgent attention from policy makers to make the remittance in favor of exports by developing the export strategies. In this regard, a special focus on exporting to the rich economies may be a good way to boost the export performance of Nepal.